The Secret to Success in Agriculture E-Commerce: E-Service Quality of Panenpa - Basmantra, Ida Nyoman; Supartha, Anak Agung Ayu Rika Putri; Emmerson, Melissa Fong; Candra, Sevenpri (Jurnal Ilmiah Manajemen & Bisnis, 2023)
The development of digital technology is an innovation that able to increase the country's economic growth. This development is considered as the key solutions to any problems in Indonesia. Sectors that have high potential is the agricultural sector. Agricultural e-commerce system is one the instance form of implementing digital technology in the agricultural sector. It plays a pivotal role in helping farmers to market their agricultural products and on the other hand, it provides benefits for fresh products consumers. The aim of this research is to synthesize the existing literature on the e-service systems in the agricultural fields by exploring the readiness of the e-commerce, tailored to working women/working housewives in Bali. This research used a qualitative method, and the data was collected using purposive sampling technique through the interview method. For the results, researcher founded knowledge gaps and beliefs in the domains of delivery service, product quality and payments fulfilment. To bridge identified gaps, researcher strongly suggest renewal and improvement on the lacking to meet customers satisfaction and escalate repurchase intention. For practitioners, this study is meaningful in the study of electronic service quality of agricultural e-commerce to understand customer’s motivation and expectations towards the use of e-service.